Henotheising Paganism and the Religion of Abraham in Late Antiquity - Stroumsa, Guy G. (ARYS. Antigüedad: Religiones y Sociedades, 2024)
This article seeks to contribute to a better understanding of the dynamics between monotheistic and polytheistic conceptions in Late Antiquity, in particular in relation to the Hypsistarians. It does so through an analysis of Abraham’s status as a culture hero beyond Jewish and Christian milieus. The article also insists on the fact that one must speak of continuum rather than of polarity between the various theological attitudes. Through a close reading of some essential testimonies, it highlights the fundamental fluidity of traditional categories in the History of Religions, such as monotheism and polytheism, as well as the dialectics between popular religion and that of philosophers, or between universalism and particularism. It also offers a new suggestion about the origin of the puzzling Qur’anic concept of ḥanīf.
Keywords: Abraham; Ḥanīf; Hanputa; Julian; Marinus; Sozomen; Theos Hypsistos